Crystal structure of ferric recombinant horseradish peroxidase - Mst Luthfun Nesa; Suman K. Mandal; Christine Toelzer; Diana Humer; Peter C. E. Moody; Imre Berger; Oliver Spadiut; Emma L. Raven (JBIC Journal of Biological Inorganic Chemistry, 2025)
Horseradish peroxidase (HRP), isolated from horseradish roots, is heavily glycosylated, making it difficult to crystallize. In this work, we produced recombinant HRP in E. coli and obtained an X-ray structure of the ferric enzyme at 1.63 Å resolution. The structure shows that the recombinant HRP contains four disulphide bonds and two calcium ions, which are highly conserved in class III peroxidase enzymes. The heme active site contains histidine residues at the proximal (His 170) and distal (His 42) positions, and an active site arginine (Arg 38). Surprisingly, an ethylene glycol molecule was identified in the active site, forming hydrogen bonds with His 42 and Arg 38 at the δ-heme edge. The high yields obtained from the recombinant expression system, and the successful crystallization of the enzyme pave the way for new structural studies in the future. Graphical abstract

Characterizing the Biological Community before and after Partial Removal of an Offshore Gas Platform in the Northwestern Gulf of Mexico - Michelle A. Johnston; Marissa F. Nuttall; Emma L. Hickerson; Kelly O’Connell; Raven D. Blakeway; John A. Embesi; Jimmy MacMillan; Douglas Peter; George P. Schmahl (Environmental Management, 2022)

Do Oil and Gas Lease Stipulations in the Northwestern Gulf of Mexico Need Expansion to Better Protect Vulnerable Coral Communities? How Low Relief Habitats Support High Coral Biodiversity - Marissa Faye Nuttall; Emma L. Hickerson; Raven D. Blakeway; George P. Schmahl; Paul W. Sammarco (Frontiers in Marine Science, 2022)
The continental shelf of the northwestern Gulf of Mexico harbors extensive reefs and banks that support diverse coral reefs and mesophotic communities. Mesophotic communities range in depth from 40 to 200 m and, in this region, foster some of the densest coral forests [aggregations of mesophotic octocoral, antipatharian, and branching stony coral communities] reported in published literature (10.23 ± 9.31 col/m 2 ). The geologic features underlying the exposed substrates that harbor mesophotic communities are targeted for extensive hydrocarbon exploration and extraction, as they often contain oil and/or natural gas. The Bureau of Ocean Energy Management regulates offshore energy development in the United States and is tasked with protecting sensitive biological communities from impacts related to oil and gas activities. This study analyzed alpha and beta diversity of mesophotic coral forests on fourteen topographic banks in the northwestern Gulf of Mexico. The objective of the study was to examine differences in structure and community in relation to lease stipulations established by the Bureau of Ocean and Energy Management. It was determined that dense and diverse mesophotic coral forests and carbonate producers exist in present regulatory zones that prohibit oil and gas activities; however, the coral communities exist in higher densities, diversity, and richness in low relief substrates outside of these regulatory zones. Our findings suggest low relief hard substrates serve as important habitat for mesophotic coral forests; thus, we suggest the expansion of current stipulations should be considered to provide better protection to vulnerable coral communities on low relief features. Furthermore, additional studies to refine the relationship between low relief structures and biodiversity are needed to develop more meaningful habitat definitions to support resource management and improve resource protection in the future.

Coral bleaching and recovery from 2016 to 2017 at East and West Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Emma L. Hickerson; Marissa F. Nuttall; Raven D. Blakeway; Travis K. Sterne; Ryan J. Eckert; George P. Schmahl (Coral Reefs, 2019)

Flood event attribution and damage estimation using national‐scale grid‐based modelling: Winter 2013/2014 in Great Britain - Alison L. Kay; Naomi Booth; Rob Lamb; Emma Raven; Nathalie Schaller; Sarah Sparrow (International Journal of Climatology, 2018)
A sequence of major flood events in Britain over the last two decades has prompted questions about the influence of anthropogenic greenhouse gas emissions on flood risk. Such questions are difficult to answer definitively, as a range of other factors are involved, but modelling techniques allow an assessment of how much the chance of occurrence of an event could have been altered by emissions. Here the floods of winter 2013/2014 in Great Britain are assessed by combining ensembles of climate model data with a national‐scale hydrological model and, for one severely impacted river basin (the Thames), a detailed analysis of flood inundation and the increased number of residential properties placed at risk. One climate model ensemble represents the range of possible weather under the current climate, while 11 alternative ensembles represent the weather as it could have been had past emissions not occurred. The pooled ensemble results show that emissions are likely to have increased the chance of occurrence of these floods across much of the country, with a stronger influence on longer duration peaks (~10 days or more) than for shorter durations (consistent with observations). However, there is substantial variation in results between alternative ensembles, with some suggesting likely decreases in the chance of flood occurrence, at least in some regions of the country. The influence on flows and property flooding varies spatially, due to both spatial variation in the influence on precipitation and variation in physical properties that affect the transformation of precipitation to river flow and flood impacts, including flood defences. This complexity highlights the importance of using hydrological modelling to attribute hydrological impacts from meteorological changes. Changes in snow occurrence in a warming climate are also shown to be important, with effects varying spatially.

A short history of heme dioxygenases: rise, fall and rise again - Emma L. Raven (JBIC Journal of Biological Inorganic Chemistry, 2017)

Structural and spectroscopic characterisation of a heme peroxidase from sorghum - Chukwudi I. Nnamchi; Gary Parkin; Igor Efimov; Jaswir Basran; Hanna Kwon; Dimitri A. Svistunenko; Jon Agirre; Bartholomew N. Okolo; Anene Moneke; Bennett C. Nwanguma; Peter C. E. Moody; Emma L. Raven (JBIC Journal of Biological Inorganic Chemistry, 2016)

Ascorbate peroxidase–thioredoxin interaction - Eric Gelhaye; Nicolas Navrot; Isabel K. Macdonald; Nicolas Rouhier; Emma Lloyd Raven; Jean-Pierre Jacquot (Photosynthesis Research, 2006)